Discussion - Pfleiderer, Paul (Review of Financial Studies, 1990)
The authors of this article present convincing evidence that opening prices differ from closing prices. Their major empirical finding is that returns that are measured from the opening of the market to the next open have higher variance than returns measured from the close of trade to the next close. This result is also found in Amihud and Mendelson (1987), but this article improves on the Amihud-Mendelson study by using a larger sample and by conducting a number of other tests. What is special about opening prices? The authors argue that the higher volatility of open-to-open returns is due to the strategic behavior of the specialist. The specialist sets the opening price in the call auction market that occurs at the open and is allowed to trade from his own account at this price. The authors suggest that in exploiting his monopoly position, the specialist increases the effective bid-ask...